1982
DOI: 10.1159/000137730
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of Extrapyramidal Symptoms: Interaction between Neuroleptics and Other CNS Active Drugs

Abstract: Neuroleptics were able to induce motor incoordination when administered to rats in large amounts. It has been observed that this effect could be antagonized by some CNS active drugs endowed with dopaminergic stimulants, anticholinergic and antihistaminic properties (such as amphetamine, apomorphine, atropine and diphenhydramine), only when evoked by neuroleptics (haloperidol, metoclopramide and LR 511) causing muscle rigidity. Other antihistaminics blocking H i receptors (chlorpheniramine, chlorcyclizine, cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…treatment with the 5-HT antagonist, methysergide. Conversely, other studies have reported that catalepsy was unaffected by the 5-HT antagonists, metergoline and methysergide, or by depletion of 5-HT with p-chlorophenylalanine (see, for example, Sarnek & Baran, 1975;Fregnan & Vidali, 1982).…”
Section: Introductionmentioning
confidence: 96%
“…treatment with the 5-HT antagonist, methysergide. Conversely, other studies have reported that catalepsy was unaffected by the 5-HT antagonists, metergoline and methysergide, or by depletion of 5-HT with p-chlorophenylalanine (see, for example, Sarnek & Baran, 1975;Fregnan & Vidali, 1982).…”
Section: Introductionmentioning
confidence: 96%
“…For instance, in some studies, a reduction of haloperidol-induced catalepsy was found after destruction of serotonergic neurons in the midbrain raphe or by depletion of central 5-HT stores with p-chlorophenylalanine and by blockade of 5-HT receptors with methysergide (Kostowski et al 1972;Carter and Pycock 1977;Balsara et al 1979). In other studies, haloperidol-induced catalepsy was found to be una¤ected after brain 5-HT depletion with p-chlorophenylalanine or by blockade of the 5-HT receptors with metergoline and methysergide (Sarnek and Baran 1975;Fregnan and Vidali 1982;Broekkamp et al 1988). After treatment with the 5-HT agonists quipazine and 5-methoxy-dimethyltryptamine and the 5-HT reuptake inhibitor clomipramine haloperidolinduced catalepsy was found to be enhanced (Carter and Pycock 1977;Balsara et al 1979).…”
Section: Discussionmentioning
confidence: 96%